Detect, trace and react: Danish senior centre staffs' awareness of and response to signs of deteriorating health or well‐being among senior centre users – An ethnographic field study. (7th August 2021) - Langergaard, Sofie; Rasmussen, Amanda N.; Petersen, Kirsten S.; Villumsen, Morten; Overgaard, Charlotte
Abstract: Senior centre staff members seemingly have an important organisational and administrative role, as well as engage in outreach activities, referral and follow‐up in relation to health issues among senior centre users. However, their role in health promotion and illness prevention is easily overlooked and under researched. This study aimed to explore municipal senior centre staffs' awareness of and response to signs of deteriorating health or well‐being among users. A multisite ethnographic field study was conducted at seven municipal senior centres in Denmark from November 2019 to February 2020. Data were obtained from participant observation and semi‐structured individual interviews with 16 staff members. A thematic analysis strategy helped identify themes of importance. Senior centre staff followed a process of three steps when remaining aware of and responding to signs of deteriorating health and well‐being among users: detecting, tracing and reacting. Three themes with corresponding subthemes were identified: Establishing close and trusting relationships, facilitating a community feeling and utilising joint collaboration. Each subtheme was linked to some or all of the three steps in the process. The municipal senior centre staff had a strong and explicit focus on detecting, tracing and reacting to signs of deteriorating health and well‐being among senior centre users. This makes the senior centres a promising arena for illness prevention and health promotion.